Factor of Social Media Adoption for Marketing in Industry : A Literature Review - Adisuputra, A (Jurnal Informatika Ekonomi Bisnis, 2025)
Social media has allowed people to interact freely with other people and has created a way to market products or services to fellow users who are involved in using social media. The trend of using social media for marketing (SMM) in recent years has increased and has become the choice for many industries to do marketing. Uniquely, on the other hand, the use of social media for marketing has resulted in opportunities and employment opportunities for everyone to be involved as marketing agents (endorsement), which not only provides opportunities for public figures but also for fellow social media users. This paper attempts to conduct a review to see and find out what factors make industry players use social media for marketing to support marketing. To achieve this objective, a thorough literature search was conducted using three reputable databases: IEEE, Science Direct, and Taylor & Francis. From the search results, 25 relevant papers were selected to support this research, providing valuable insight into the factors that influence the adoption of social media for marketing.